Power release in a subcritical reactor - Demchenko, P.O.; Gussev, Ye.V.; Nikolaichuk, L.I. (Вопросы атомной науки и техники, 2005)
Numerical simulation results of power release in a subcritical reactor in which the neutron field is generated under bombardment of an actinide target by a relativistic proton beam are given.